2009
DOI: 10.1037/a0013781
|View full text |Cite
|
Sign up to set email alerts
|

Electronic media and lucid-control dreams: Morning after reports.

Abstract: as well as control dreams, have recently been reported as associated with video game play (Gackenbach, 2006). In this study, dreams were collected from the morning after a night of rested sleep as well as electronic media use from the day before the dream. In a factor analysis, lucid and control dreams were associated with all electronic media use but most strongly with video game play.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 7 publications
(5 reference statements)
0
29
0
Order By: Relevance
“…For example, Gackenbach (2009) found that electronic media use was associated with lucid dreams (i.e. where the dreamer is aware he or she is dreaming while asleep) and control dreams (i.e.…”
Section: Electronic Media Use and Sleep Pattern Correlationsmentioning
confidence: 98%
“…For example, Gackenbach (2009) found that electronic media use was associated with lucid dreams (i.e. where the dreamer is aware he or she is dreaming while asleep) and control dreams (i.e.…”
Section: Electronic Media Use and Sleep Pattern Correlationsmentioning
confidence: 98%
“…Regarding the function of dissociative thought, it seems to be accompanied by a down-regulation of negative emotion in dreaming as well as in psychiatric disorders ( LaBerge and Rheingold, 1991 ; Phillips et al, 2001 ; Voss et al, 2013 ; Gackenbach and Bosveld, 2014 ). Several studies show lucidity in dreams to be associated with positive rather than with negative emotions ( LaBerge and Rheingold, 1991 ; Voss et al, 2013 ; Gackenbach and Bosveld, 2014 ), albeit most studies do not differentiate between positive feelings during the dream vs. positive feelings following awakening from a lucid dream.…”
Section: Lucid Dreams and Dissociative Mental Statesmentioning
confidence: 99%
“…Regarding the function of dissociative thought, it seems to be accompanied by a down-regulation of negative emotion in dreaming as well as in psychiatric disorders ( LaBerge and Rheingold, 1991 ; Phillips et al, 2001 ; Voss et al, 2013 ; Gackenbach and Bosveld, 2014 ). Several studies show lucidity in dreams to be associated with positive rather than with negative emotions ( LaBerge and Rheingold, 1991 ; Voss et al, 2013 ; Gackenbach and Bosveld, 2014 ), albeit most studies do not differentiate between positive feelings during the dream vs. positive feelings following awakening from a lucid dream. It is our observation (Voss et al, unpublished) that dreamers often experience their lucid dreams to be emotionally neutral, sometimes accompanied by a sense of achievement (“I did it!” and “success!”) and euphoria after awakening, both instances falling under the category of what Lewis (1995) refers to as “self-conscious emotion.” Self-conscious emotions such as guilt, shame, or empathy require the ability to reflect on the self and, therewith, frontal lobe as well as anterior insular cortex (AIC) activity ( Gu et al, 2013 ).…”
Section: Lucid Dreams and Dissociative Mental Statesmentioning
confidence: 99%
“…In this research program, we have been investigating whether video game play may be affecting the consciousness of players. Towards this end, we have found higher lucid dreaming among gamers (Gackenbach 2006;, more flow (Gackenbach 2008a), more absorption (Gackenbach 2007), and a single-minded focus on gaming (Gackenbach et al 2009). Furthermore, absorption in various forms seems to be a hallmark of gaming.…”
Section: Introductionmentioning
confidence: 95%